Implementing Needs Analysis in Curriculum and Material Development: A Study in The ESP Context - Santoso, Andi; Sanjaya, Ricky Eka (STKIP PGRI Tulungagung, 2025)
Needs analysis (NA) is a vital process in designing effective curriculum and instructional materials, particularly in English for Specific Purposes (ESP) settings. This study explores the implementation of NA in the context of ESP course design for Hotel Management students. The research applies a descriptive qualitative approach, drawing data from classroom-based documentation and lecturer-led curriculum planning. Findings reveal that incorporating NA allows for better alignment between learners' target needs, learning preferences, and instructional goals. Key tools such as questionnaires, interviews, placement tests, and focus group discussions were used to gather data from learners and stakeholders. The study highlights how NA supports learner-centred instruction, improves motivation, and leads to more contextually relevant teaching materials. The article concludes by emphasizing the role of NA as a foundational step in curriculum and material development, especially in professional and vocational English settings.